If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12T + -8th = -52 Solving 12T + -8ht = -52 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '8ht' to each side of the equation. 12T + -8ht + 8ht = -52 + 8ht Combine like terms: -8ht + 8ht = 0 12T + 0 = -52 + 8ht 12T = -52 + 8ht Divide each side by '12'. T = -4.333333333 + 0.6666666667ht Simplifying T = -4.333333333 + 0.6666666667ht
| 12n6= | | 7-(4n-2)=2-5n | | 5(r-1)=20 | | 3(9+c)=2(3+c) | | 11x-8+2x-4=10x-3+2x | | 11u-6u=20 | | 12x+43=274 | | -2-36= | | 4x+10=3x+3+x-9 | | log[5](x-10)-log[5](3)=2 | | 2x^2+11x=4 | | 37x+12y=5 | | 230=-23 | | 8+2x=-7 | | f=(-16) | | x-43=888 | | -63+7x=0 | | n=11 | | (.5x+1.2)-(3.6-4.5x)=(4.8-0.3x)+(10.5x+.6) | | x+23=143 | | 7r+2=5(4-4) | | 78.6=3.14 | | x+5=123 | | -3-6n=4+n | | 210+.53x=341.44 | | 4w+3=3(w+5) | | 4x=-35 | | a+-3=-91 | | 9x-13=127-11x | | 10+5x-25=50-15 | | x^4+2x^3+2x^2-4x-16=0 | | (y+4)-(y-1)=6y |